2022
DOI: 10.1021/jacs.1c10651
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Dynamic Disorder, Not Ionic Trapping, Controls Charge Transport in Highly Doped Conducting Polymers

Abstract: Doped organic semiconductors are critical to emerging device applications, including thermoelectrics, bioelectronics, and neuromorphic computing devices. It is commonly assumed that low conductivities in these materials result primarily from charge trapping by the Coulomb potentials of the dopant counterions. Here, we present a combined experimental and theoretical study rebutting this belief. Using a newly developed doping technique based on ion exchange, we prepare highly doped films with several counterions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
80
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 72 publications
10
80
1
Order By: Relevance
“…Overall, these conclusions are in line with the recent work of Jacobs et al on the influence of para -crystallinity measured in the π-stacking direction on the charge transport properties in doped polymer semiconductors. 44 As a side remark, the polymorphism of PBTTT- 8 O evidenced in the pristine films seems to have little influence on the TE performances of doped films.…”
Section: Resultsmentioning
confidence: 97%
“…Overall, these conclusions are in line with the recent work of Jacobs et al on the influence of para -crystallinity measured in the π-stacking direction on the charge transport properties in doped polymer semiconductors. 44 As a side remark, the polymorphism of PBTTT- 8 O evidenced in the pristine films seems to have little influence on the TE performances of doped films.…”
Section: Resultsmentioning
confidence: 97%
“…Compared with an almost 1:1 ratio of edge-on and face-on orientations for gNR-CF , the films cast from FAs show crystallites with a very high ratio of edge-on orientations, 94.8, 86.3, and 84.2% for gNR-6FOH , gNR-3FOH , and gNR-9FOH , respectively. Therefore, the predominance of edge-on orientation and tighter molecular packing for FA cast films are conducive to the effective charge transport in the parallel direction of the device architecture. , To gain insight into the crystallinity difference of gNR in thin films, coherence lengths (CLs) and paracrystalline disorder ( g ) were calculated from the width of the π–π stacking diffraction peaks (CL = 2π K /FWHM, K = 0.9, ). , As shown in Figure S16c, the gNR thin films formed with FAs displayed further enhanced crystalline packing: the CL values of the (010) peaks along the IP direction increased from 47.9 Å for CF to 59.5 Å for 3FOH, 71.5 Å for 6FOH, and 54.9 Å for 9FOH. Meanwhile, the CLs of the emerging (020) peak were also calculated to be 60.8 Å for 3FOH, 93.0 Å for 6FOH, and 59.4 Å for 9FOH; the largest CLs of the films in both (010) and (020) peaks endow gNR-6FOH the highest electron mobility. ,, In addition, the lower paracrystalline disorder of π–π stacking for FA cast films (Figure S16d) also suggests the further structural ordering, which leads to a reduction of the number of structural trapping sites for the electron carriers and indicates a strong correlation with charge transport properties. , It is worth noting that the combination of edge orientation predominance, closer molecular stacking, and enhanced crystallinity always leads to a more effective electronic transport; i.e., gNR-6FOH possesses the highest 1.78 × 10 –2 cm 2 V –1 s –1 compared to 1.25 × 10 –2 cm 2 V –1 s –1 for gNR-CF , owing to its highest edge-on orientation ratio, closest distance and maximum coherence length, and lowest paracrystalline disorder for (020) π–π stacking .…”
Section: Resultsmentioning
confidence: 99%
“…). 59,60 As shown in Figure S16c, the gNR thin films formed with FAs displayed further enhanced crystalline packing: the CL values of the (010) peaks along the IP direction increased from 47.9 Å for CF to 59.5 Å for 3FOH, 71.5 Å for 6FOH, and 54.9 Å for 9FOH. Meanwhile, the CLs of the emerging (020) peak were also calculated to be 60.8 Å for 3FOH, 93.0 Å for 6FOH, and 59.4 Å for 9FOH; the largest CLs of the films in both ( 010) and (020) peaks endow gNR-6FOH the highest electron mobility.…”
Section: T H I S C O N T E N T Imentioning
confidence: 89%
See 1 more Smart Citation
“…The effects of internal dihedral rotation upon the emission spectrum and efficiency of conjugated polymer thin films have been studied experimentally, 11 while in highly doped conjugated polymers, paracrystalline disorder, rather than the ionic size of the doping ions, has been shown to control charge transport. 12 Predicting crystal structures of different conjugated polymers and how this structure impacts their properties is a current area of research; 13 however, a higher degree of crystallinity has been shown to not necessarily lead to an increase in charge-carrier mobility. 14 Recently, cryogenic tunnelling electron microscopy has been used to study the nanoscale structure of CPNs.…”
mentioning
confidence: 99%